ANALISIS KETERAMPILAN BERBICARA DENGAN MENGGUNAKAN METODE STORYTELLING PADA SISWA KELAS 1 SEKOLAH DASAR - Vany Diah Puspita Sari (INOPENDAS: Jurnal Ilmiah Kependidikan, 2022)
The purpose of this research is to determine the speaking skills of first graders using the storytelling method, and to find out the factors that cause weak speaking skills of 1st grade students of SDIT AL Hikmah Mayong Jepara. The type of research that the researcher uses is descriptive qualitative, while the subject is taken using a purposive sampling technique with a total of 6 students. Researchers conducted classroom observations and teacher interviews, then classified students' speaking skills into three categories, namely high, medium and low. The results showed that there were 6 students who had high speaking skills, 12 students had moderate speaking skills, and 10 students had speaking skills. low. One of the factors that cause students to have high speaking skills is that students have the confidence to tell stories and students are often invited to communicate by their families when at home, while the factors that cause these students to have moderate speaking skills are students already have self-confidence, but students do not fluently with the pronunciation of the sentence, it is because students are not used to speaking well. And the factors that cause students to have low speaking skills are students are shy and feel afraid to tell stories in public places